2015
DOI: 10.1186/s12879-015-0962-4
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-specific assessment of the immunological status of various groups in a leprosy endemic region

Abstract: BackgroundSerological tests can be important tools to assist in the diagnosis of leprosy and can contribute to an earlier diagnosis. The aim of this study was to evaluate the antibody responses against phenolic glycolipid-1 (PGL-1), natural disaccharide linked to human serum albumin via an octyl (NDO-HSA), Leprosy IDRI Diagnostic-1 (LID-1) and natural disaccharide octyl - Leprosy IDRI Diagnostic-1 (NDO-LID) in leprosy patients, household contacts of patients and the general population.MethodsEnzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 21 publications
7
19
0
8
Order By: Relevance
“…Our study showed IgM anti-PGL-1 antibody levels significantly higher in MB patients and lower in PB, while LL patients had higher antibody levels compared to TL and DL patients. Frota et al [28] and Fabri et al [29] had also reported higher serum levels of IgM anti-PGL-1 in MB patients compared to those IgM levels observed in PB patients, corroborating our results.…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed IgM anti-PGL-1 antibody levels significantly higher in MB patients and lower in PB, while LL patients had higher antibody levels compared to TL and DL patients. Frota et al [28] and Fabri et al [29] had also reported higher serum levels of IgM anti-PGL-1 in MB patients compared to those IgM levels observed in PB patients, corroborating our results.…”
Section: Discussionsupporting
confidence: 92%
“…17 These difficulties can favor transmission and physical disabilities. 6 In view of the results obtained in the research, it was observed that the majority of participants were MB cases (86.1%), and therefore the risk of falling ill among household contacts was very significant, since case contacts with classification MB are more exposed and prone to M. leprae infection 18 and, therefore, are at higher risk of becoming ill, compared to contacts of paucibacillary (PB) cases. 19 Other factors that may interfere with the development of leprosy, such as the characteristics of coexistence and the exposure of the contact with the case within the home, may be the reason for the greater risk of getting sick from the contacts who lived at the time of diagnosis.…”
Section: Resultsmentioning
confidence: 93%
“…The blood collected in VACUTAINER® BD tube with separator gel and vacuum adaptation was fractionated in aliquots of 500 μl of serum, stored in a freezer, duly identified. The ELISA test to analyze the presence of anti-PGL-1 IgM antibodies was performed according to standard protocol (6) . For the examination, the natural-octyl-HSA disaccharide (ND-O-HSA) was used.…”
Section: Methodsmentioning
confidence: 99%
“…ELISA Index values greater than 1.10 were considered positive. The reading was in a spectrophotometer at 492 nm of absorbance (6) . The ELISA was repeated for samples displaying ELISA index values, classified as positive in a single well of the duplicate, and samples whose values exhibited 25.0% or more of variation between the duplicate (10) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation